The global engineering deans council: transforming engineering education in a time of change - A. K. Ashmawy (Высшее образование в России, 2022)
The paper presents the history of the Global Engineering Deans Council (GEDC) creation and activities carried out by this international educational organization. The “global engineer”is defined from the perspective of this organization; the global engineering projects in Dubai are described. Moreover, the prospects for the development of engineering education in themodern global world are given.